GALICH LAND SON - Gaydabura, V. L. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
In the article the creation of the Ukrainian producer is explored Ivan Kogutyak, which headed a theater in Colomyia in the first decades of the ХХ century. Attempt to restore separate presentations of collective was done, and also analyzed activity of I. Kogutyak theater in the context of national-spiritual life of not only Colomyia but also Western Ukraine on the whole.